Efficacy of Sodium Silicate on Aspergillus flavus and its Action on Cell Wall Degrading Enzymes with Molecular Docking Studies - Aisha M. H. Al-Rajhi; Abeer S. Albalawi; Nahlah N. Albakri; Abeer M. Almutrafy; Ahmad Alhujaily; Soad K. Al Jaouni; Samy Selim (BioResources)
The extent of spoilage of fruits and vegetables increases post harvest, and fungi is one of the greatest causes. The effect of sodium silicate on Aspergillus flavus and its cell wall degrading enzymes, namely polygalacturonic acid transeliminase (PGTE), pectin methyltranseliminase (PMTE), and pectin lyase (PL), was investigated via molecular docking. At the 4th day, 100 mM of sodium silicate completely inhibited A. flavus, while it reflected 79.70, 61.16, 56.82, and 37.23% inhibition at 6, 8,10, and 12 days, respectively. The PGTE (369.33 ± 2.08 U/mL) showed maximum activity at 8th day in the medium without sodium silicate, also at 20 to 80 mM sodium silicate, their maximum activity was recorded at the 8th day, while it reached to maximum at 10th day in the medium with 100 mM sodium silicate. The PMTE recorded highest activity at the 6th day (414.00 ± 1.73 U/mL) without sodium silicate, at 8th day when sodium silicate ranged from 20 to 80 mM, and at 10th day (97.67 ± 1.25 U/mL) with 100 mM sodium silicate. Day 8 was optimum for PL activity. Sodium silicate demonstrates potent interaction with the active sites of the studied proteins, suggesting its potential as a molecular inhibitor of studied enzymes.